Overexpression of Outer Membrane Protein X (OmpX) Compensates for the Effect of TolC Inactivation on Biofilm Formation and Curli Production in Extraintestinal Pathogenic Escherichia coli (ExPEC) - Li, Binyou; Huang, Qi; Cui, Ailian; Liu, Xueling; Hou, Bo; Zhang, Liyuan; Liu, Mei; Meng, Xianrong; Li, Shaowen (Frontiers in Cellular and Infection Microbiology, 2018)
Our previous study showed that the inactivation of the efflux pump TolC could abolish biofilm formation and curli production of extraintestinal pathogenic Escherichia coli (ExPEC) strain PPECC42 under hyper-osmotic conditions. In this study we investigated the role of OmpX in biofilm formation and curli production of ExPEC PPECC42. Our data showed that OmpX disruption or overexpression didn’t significantly affect the biofilm formation and curli production of the wild-type strain. However, in the tolC-deleted mutant, overexpressing OmpX suppressed the effect of TolC inactivation on ExPEC biofilm formation and curli production under hyper-osmotic growth conditions. Real-time qRT-PCR confirmed that OmpX overexpression affected curli production by regulating the transcription of the curli biosynthesis-related genes in the ΔtolC strain. Our findings suggest that OmpX is involved in biofilm formation and curli production.